Risk Assessment And Patient Safety In Physiotherapy Practice: A Comprehensive Analysis Of Factors Contributing To Patient Falls - Alpiah , Dini Nur; Alfian, RM; Handayani, Dwi Ratna Sari; Waluyo, Imam; Subu, Muhammad Arsyad; Khanna, GL (Indonesian Scientific Publication, 2024)
Risk assessment is a systematic procedure employed to detect potential dangers and evaluate the possible consequences of disasters or calamities, ensuring comprehensive hazard identification in the work environment. Integrating risk assessment into management and organizational processes is crucial, especially in healthcare settings like physiotherapy, where patient safety is paramount. This comprehensive review systematically compiled and analyzed relevant studies from scholarly journals, bibliographies, and related articles to evaluate the effectiveness of risk assessment procedures in identifying and mitigating potential hazards in physiotherapy practice. The review specifically focused on the use of the STEADI tool in conjunction with electronic health records (EHR) for joint risk assessments. The risk assessment process involves three key stages: identification, calculation, and implementation of control measures. Various methodologies were explored, including models like CATCH fall administration, PISTI management, multidisciplinary collaboration, and Fall TIPS. Falls, a major global health issue, are the 13th leading cause of death worldwide, with preventive strategies shown to reduce fall-related deaths by up to 92%. Effective risk assessment is essential for ensuring patient safety in physiotherapy. By identifying and mitigating potential risks, particularly those related to falls, healthcare providers can significantly improve patient outcomes and safety in clinical practice.